Sources of variability in single grain dose recovery experiments: Insights from Moroccan and Australian samples - Doerschner, Nina; Hernandez, Marion; Fitzsimmons, Kathryn E. (Ancient TL, 2016)
In our study, we investigate the quartz singlegrain dose recovery characteristics of five aeolian samples from three archaeological sites in Australia and Morocco. Comparatively small (20 – 49 Gy) and high (180 – 208 Gy) doses were applied to sand-sized quartz grains of each sample. Samples were bleached by green laser, sunlight and solar simulator stimulation. We observed a primary dependency of the results on the size of the administered dose, but also observed sample-specific responses to the chosen dose recovery measurement parameters. The Australian samples originate from an openair archaeological site and consist of highly sensitized quartz grains with comparatively small equivalent doses. By contrast, the Moroccan samples originate from two cave sites known to be affected by heterogeneous dose rates and post-depositional mixing to varying degrees; this material is generally less sensitive, and expected equivalent doses are > 180 Gy, while single-grain quartz weighted average signal saturation levels (2D0) exceed 235 Gy. Single grains from all sites, with one exception, recover small applied laboratory doses. These fall within 5 % of unity irrespective of the bleaching method. However, when applied doses are high, dose recovery test results vary substantially depending on how individual samples respond to the bleaching treatment prior to the given dose. The lowest dose recovery ratios and highest overdispersion values were observed in samples bleached in the solar simulator. Our results highlight the importance of investigating dose recovery characteristics at single grain level, and indicate additional sources of complexity in understanding the luminescence characteristics of quartz.